Gestión de la calidad de los servicios en PC soluciones, de la ciudad de Babahoyo en el periodo 2022. - Avilés Martínez, Ashly Daniela (2023)
The objective of this case study is to analyze the quality of the services offered by the microenterprise PC Soluciones in the city of Babahoyo, by identifying the factors and activities that directly or indirectly contribute to the experience, therefore, in the customer satisfaction and loyalty. Determine the processes carried out by the business in order to recognize failures and risks, obtain the perception and criteria of the clients, through the root cause analysis method, the survey techniques and Service Blueprint with their respective instruments, established as the means to achieve the objectives of this work. The results obtained through the application of the techniques indicated that some of the factors that affect PC Soluciones customer service are related to the lack of control and organization within the establishment, not applying loyalty and digital marketing strategies, among others. Thus, based on these deficiencies, improvement strategies are prepared, which are proposed in the form of a recommendation in this document.